Examine the Relationship between Mindfulness and Drug Craving in Addicts Undergoing Methadone Maintenance Treatment. - Ali Ardame; Soodabe Bassaknejad; Yadollah Zargard; Parisa Rokni; Mehdi Sayyah (Tehran University of Medical Sciences, 2014)
The aim of this study was examination the relationship between mindfulness and drug craving in addicts undergoing methadone maintenance treatment.The subjects of this research were 80 addicts undergoing methadone maintenance treatment selected through available sampling from four addiction treatment center in Ahvaz from March 2012 to September 2012. Two questionnaires to examine the variables of this study were the five facets mindfulness questionnaire (FFMQ) and hero-in craving questionnaire (HCQ). The data were analyzed using SPSS version 16.The Pearson correlational results indicated significant reverse relation between mindfulness factors and craving sub scales (P